BOUNDS ON STEADY STATE FLOW STRENGTHS OF MULTIPHASE ROCKS: THEORY AND TEST WITH EXPERIMENTAL DATA - Zhou S. (My University, 1995)
Constraints on steady state flow strengths of multiphase aggregates can be obtained by the bounds calculated using the assumption of uniform stress and uniform strain rate within the aggregate. This study shows that such strength bounds are virtually identical to the strength bounds derived from the self-consistent theory and strain energy minimization criterion. A test on the validity of strength bound theory is made using experimental data, which show that such theory is generally valid for common crustal rocks such as granite, diorite and diabase (gabbro). It is also shown that the relative contrast of such strength bounds increases with the decrease in the overall strain rate, particularly at geologically plausible strain rates where they are at least greater than an order of magnitude in difference. A new approach, proposed here, is to take either the upper bound, derived from the self-consistent theory or the lower bound, derived from the constant volume creep assumption, depending on either constant stress or constant strain rate experiments, as an estimate of multiphase rock strength. This approach is tested against available experimental data, which show that this new model is generally more consistent than the Voigt-Reuss-Hill model, with relative error always less than 100% for wide ranges of temperatures and strain rates.